2010
DOI: 10.1111/j.1540-8191.2008.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Off-pump Coronary Artery Bypass Surgery Among Patients with Malignant Disease

Abstract: We believe that staged operation to treat coronary artery disease and malignancy can be performed safely. The use of off-pump technique to revascularize the myocardium can be performed without any complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
0
20
0
2
Order By: Relevance
“…Optimal treatment strategies for simultaneously diagnosed esophageal cancer and CAD remain debatable. The two associated procedures are performed simultaneously by a one-staged operation [19,20] or separately by two-staged operations [21, 22]. CAD leads to surgical morbidity of patients with malignant disease, and cardiac revascularization should be carried out first to avoid perioperative risk of myocardial ischemia or infarction and cardiac dysfunction [23].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal treatment strategies for simultaneously diagnosed esophageal cancer and CAD remain debatable. The two associated procedures are performed simultaneously by a one-staged operation [19,20] or separately by two-staged operations [21, 22]. CAD leads to surgical morbidity of patients with malignant disease, and cardiac revascularization should be carried out first to avoid perioperative risk of myocardial ischemia or infarction and cardiac dysfunction [23].…”
Section: Discussionmentioning
confidence: 99%
“…A recent trend has been the use of off-pump CABG to avoid the effect of cardiopulmonary bypass and decrease the use of heparin (10,14,15). The off-pump technique could markedly lower the risk of the disadvantages related to use of cardiopulmonary bypass, although other studies found no advantage of using an off-pump technique compared with cardiac surgery using cardiopulmonary bypass (3,(13)(14)(15). The present study demonstrated that concomitant OPCAB and non-cardiovascular surgery compared with those of isolated OPCAB did not increase operative mortality and perioperative morbidities, although the majority of patients had concomitant malignant disease and underwent laparotomy (63 patients had combined malignant diseases; 62 patients underwent general surgeries opening the abdominal cavity).…”
Section: Discussionmentioning
confidence: 98%
“…Surgical treatment can be performed separately by 2-stage operations or simultaneously by a concomitant operation. The 2-stage procedure, prior successful CABG followed by non-cardiovascular surgery, has been demonstrated to reduce mortality and morbidities; however, this technique was associated with higher cost, delay in surgery for malignant disease, and longer hospital stay (2,3,8). An unpredictable delay between the two procedures could be detrimental in cases of malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Resim 1-3) Nadiren de olsa sol anterolateral veya posterolateral torakotomiyle yapılan olgular da mevcuttur (Resim 4-7). Bu ameliyatları pompa kullanmaksızın (Off-pump) yapmayı tercih eden cerrahlar da mevcuttur (20,21,22). Her iki tür operasyonun da avantaj ve dezavantajlarını ifade eden çok sayıda yayın vardır.…”
Section: İskemi̇k Kalp Hastaliklari Ve Akci̇ğer Hastaliklariunclassified